The efficacy and safety of subcision using CO2 gas combined with fractional laser for acne scars: Clinical and microscopic evaluation. (2nd October 2016) - Lee, Sang Jun; Suh, Dong Hye; Chang, Ka Yeon; Kim, Hyun Joo; Kim, Tae In; Jeong, Ki-Heon; Shin, Min Kyung; Song, Kye Yong
Abstract : Background: Various modalities have been used to treat acne scars. CO2 fractional laser is an effective and commonly used treatment. CO2 gas injection into the dermis by needle with high pressure can cause fibrotic collagen breakage, producing the effects of subcision. CO2 also stimulates collagen synthesis by increasing neovascularization and releasing oxygen.Objective: This study evaluated the efficacy and the safety of the combined treatment with CO2 gas subcision and CO2 fractional laser for acne scars.Methods and materials: Fourteen patients with acne scars were treated with three sessions of CO2 gas subcision at 2-week intervals and two sessions of fractional laser at 4-week interval. The clinical improvement was assessed using a 4-point scale. For histologic analysis, punch biopsy was performed before and after treatment in 10 patients.Results: All patients experienced clinical improvements. Excellent, marked, moderate, and mild response was achieved in 1 (7%), 8 (57%), 4 (29%), and 1 patient (7%), respectively. Histologic evaluation of the biopsy specimens showed increased dermal collagen with dermal thickening and elastic fiber straightening in the reticular dermis after the treatment.Conclusion: The combination therapy with CO2 gas subcision and fractional laser was satisfactory and safe for treating acne scars. Abbreviation and acronym: CO2 : Carbon dioxide GAS: Global assessment scale H&E: hematoxylin and eosin; SD: standard deviation